The Affecting of Media Usage on Political Trust and Corruption in Thailand - Jinarat, Veerasak (Dhammathas Academic Journal, 2025)
The objective of this research is to study the predication of social media usage on political trust and corruption in Thailand. Quantitative research was used in collecting 1,600 respondents of the opinions of generation X, Y, Z who live in Thailand. The research tools is the questionnaire with .883 of validity test. The statistical analysis are mean, percentage, standard deviation, t-test and multi-regression analysis. The findings show that: 1) Social media usage could predict significantly to political trust at Beta = -.05, t = -2.86 (Sig .004). 2) Political trust could not predict significantly to political trust at Beta = .02, t = 1.08 (Sig .277). 3) Social media usage and attitude to government unit except political interest, predicted significantly and simultaneously to political trust, the value of coefficient of determination is R2 = .65, Std. error = .84, F = 662.95 (Sig .000). 4) Media usage predicted significantly lower than attitude to government unit, to political trust such as justice system, public service, police department, transportation, public health system and local government at Beta = .31, .15, .18. .20, .07 and .07, (Sig .00 and .01), respectively. 5) The findings conclude that only the component of political trust in terms of trust in politician could predict significantly to corruption at Beta = .06, t = 2.16 (Sig .031). Therefore, politician’s keeping words is the most crucial factor, could effect on people’s political trust.